Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851) - Brugnera, Ricardo; Roell, Talita; Campos, Luiz Alexandre; Grazia, Jocelia (Zootaxa, 2020)
Some species of Podisus Herrich-Schäffer have a confuse taxonomic history with several modifications and loss of information over time. The genus has been considered a taxonomic dumping ground in Asopinae, and its current species composition is doubtful. After examining the type specimens of Telepta distincta Stål, Arma submarginata Walker, Arma monospila Walker, Arma fuscescens Dallas, Arma caliginosa Walker, Arma turbida Walker and Podisus mellipes Bergroth, we redescribe and revalidate A. fuscescens as Podisus fuscescens rev. stat., previously considered a junior synonym of Podisus sagitta (Fabricius). The taxonomic status, morphology and distribution of P. fuscescens and P. distinctus are updated and illustrated. Arma caliginosa, A. turbida and Podisus mellipes become synonyms of P. fuscescens. Additionally, Arma submarginata Walker is removed from its synonymy with Podisus ventralis (Dallas) and treated as a synonym of P. distinctus. Podisus signoreti Fallou is removed from its synonymy with P. distinctus and treated as species inquirenda.